Concrete Products from Waste Materials - Turdimurod o’g’li, Jovliyev Qo’ldosh; Shahriyor, Abduvohidov; Aziza, Kuldasheva (European Journal of Life Safety and Stability (2660-9630), 2021)
There are given physic-properties results of waste analysis from mining material wastes and using of them in building material industry. the amount of complete residue of the sand in the № 5 sieve is A0,63= 39% <50%, and the modulus of coefficient is Ms = 4.51 <5, so the sand belongs to the group of coarse sands. Therefore, in terms of its granular composition, sand is considered suitable for concrete preparation, and it is recommended to improve its quality by adding fine sand to its granular composition for use in concrete preparation.